2016
DOI: 10.1093/cercor/bhw104
|View full text |Cite
|
Sign up to set email alerts
|

Here Comes Trouble: Prestimulus Brain Activity Predicts Enhanced Perception of Threat

Abstract: Research on the perceptual prioritization of threatening stimuli has focused primarily on the physical characteristics and evolutionary salience of these stimuli. However, perceptual decision-making is strongly influenced by prestimulus factors such as goals, expectations, and prior knowledge. Using both event-related potentials and functional magnetic resonance imaging, we test the hypothesis that prior threat-related information and related increases in prestimulus brain activity play a key role in subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 107 publications
3
52
3
Order By: Relevance
“…Hence, whereas the amygdala might rapidly code for emotional salience6869, STG activity could more slowly subserve conscious threat perception. Supporting this account, it has been recently shown that threatening faces increase both STG and amygdala activation, but only STG reactivity correlates with emotion recognition accuracy70.…”
Section: Discussionmentioning
confidence: 88%
“…Hence, whereas the amygdala might rapidly code for emotional salience6869, STG activity could more slowly subserve conscious threat perception. Supporting this account, it has been recently shown that threatening faces increase both STG and amygdala activation, but only STG reactivity correlates with emotion recognition accuracy70.…”
Section: Discussionmentioning
confidence: 88%
“…Theories regarding expectancy bias have suggested that cues indicating an emotional event, particularly a negative event, alter emotional states and thus attention towards the event (Tomarken et al, 1989;de Jong et al, 1995;Davey and Dixon, 1996;Lin et al, 2012Lin et al, , 2014bSussman et al, 2017). Consistent with these theories, a behavioral study by Aue et al (2013) reported slower response times in identifying neutral stimuli when participants had expected the occurrences of negative stimuli than those of neutral stimuli.…”
Section: Introductionmentioning
confidence: 86%
“…When the cues indicate upcoming emotional consequences, the cues might pre-activate the attentional mechanisms before the consequences and enhance vigilance attention afterward (e.g., Tomarken et al, 1989;de Jong et al, 1995;Davey and Dixon, 1996;Lin et al, 2012Lin et al, , 2014bAue et al, 2013;Sussman et al, 2017). While uncertain cues also enhance attention to upcoming events (e.g., Nitschke, 2011, 2013;Dieterich et al, 2016Dieterich et al, , 2017; for a review, Anselme, 2010), the enhanced attention elicited by certain cues is thought to be stronger than that elicited by uncertain cues in the context of implicit expectations (Lin et al, 2018).…”
Section: The Erp Effects Of Cue Uncertainty In the Emotional Cue Condmentioning
confidence: 99%
See 2 more Smart Citations